Environmental conservation of Baduy indigenous society in disaster mitigation and food self-sufficiency based on local wisdom - Ardiansyah Bagus Suryanto (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The Baduy people have life values and a way of survival by adhering to customary laws that are inherited from generation to generation. This study examines the environmental conservation practices of the Baduy indigenous community as a form of disaster mitigation and food self-sufficiency based on local wisdom, highlighting their ecological resilience and sustainable resource management practices. Methods: Using a qualitative ethnographic approach, data were collected through indepth interviews, field observation, and literature review, to explore local wisdom practices and their implications for sustainability outcomes. Findings: In this study, disaster mitigation refers to systematic efforts to reduce disaster risks through both structural and non-structural approaches. Within indigenous contexts, mitigation is embedded in cultural practices, spatial arrangements, and ecological ethicts that function preventively rather than reactively. Thus, mitigation in the Baduy context is operationalized through land-use restrictions, settlement zoning based on topography, and sustainable agricultural systems. These practices are reinforced through customary knowledge passed down across generations, which guides community behavior in managing environmental risks. The integration of ecological awareness and traditional norms strengthens community resilience and ensures long-term sustainability of natural resources while minimizing vulnerability to disasters such as floods, landslides, and environmental degradation in daily life. Conclusion: These findings provide practical implications for policymakers, especially in integrating indigenous land-use systems into regional spatial planning and strengthening local food resilience strategies amid global environmental change. Novelty/Originality of this article: Importantly, this study highlights that the Baduy model offers transferable principles for community-based disaster risk education, particularly in land-use zoning, ecological ethics, and localized food systems.